2004
DOI: 10.1111/j.1365-2788.2005.00663.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and management of challenging behaviours in congregate and noncongregate community‐based supported accommodation

Abstract: Changes in reported and observed challenging behaviour over a 10-month period were slight. The use of evidence-based behavioural technologies for the reduction of challenging behaviour may have led to better outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 17 publications
4
62
1
Order By: Relevance
“…Meta-analytic studies reveal that the most effective interventions are those based on applied behavior analysis (Harvey et al 2009;Kahng et al 2002;Meyer and Evans 2006) with limited evidence that psychopharmacological interventions are effective (Singh et al 2005;Tyrer et al 2009) despite their widespread use (Molyneux et al 1999;Robertson et al 2000). However, behavioral interventions are labour and resource intensive for severe challenging behavior and consequently rarely available (Oliver et al 1987;Robertson et al 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Meta-analytic studies reveal that the most effective interventions are those based on applied behavior analysis (Harvey et al 2009;Kahng et al 2002;Meyer and Evans 2006) with limited evidence that psychopharmacological interventions are effective (Singh et al 2005;Tyrer et al 2009) despite their widespread use (Molyneux et al 1999;Robertson et al 2000). However, behavioral interventions are labour and resource intensive for severe challenging behavior and consequently rarely available (Oliver et al 1987;Robertson et al 2005).…”
Section: Introductionmentioning
confidence: 97%
“…While the idea that individuals with DD can suffer from mental illness has been largely accepted since the late 1980s, this is still an underserved and poorly studied population [34][35][36]. Historically, it was thought that the cognitive limitations inherent in individuals with DD precluded the development of emotional disorders.…”
Section: Mental Illness As a Contributor To Aggressionmentioning
confidence: 98%
“…The quality of life for people with disability is no doubt highly related to the quality of care provided within the housing setting (Cooper et al 2005;Evans et al 2003;Fakhoury et al 2002;Kelly and Winkler 2007;Robertson et al 2005;Sergeant and Brown 2004;Tsemberis and Eisenberg 2000), but there is strong evidence to suggest that quality of life is also related to factors present within the physical care environment (Parker et al 2004). Although it is difficult to determine the causal attribution between place and care, Moos and Lemke (1980) earlier reported that the workforce who operate in well designed residential settings provide residents with more choice in their daily activities and more influence on operational policies (Parker et al 2004).…”
Section: Care and Support And Building Designmentioning
confidence: 99%